Supercritical Carbon Dioxide Extracts of Cordyceps sinensis: Chromatography-based Metabolite Profiling and Protective Efficacy Against Hypobaric Hypoxia - Mishra, Jigni; Khan, Washim; Ahmad, Sayeed; Misra, Kshipra (Frontiers in Pharmacology, 2021)
The toxicity and disposal concerns of organic solvents used in conventional extraction purposes has entailed the need for greener alternatives. Among such techniques, supercritical fluid extraction (SFE) has gained popularity by yielding extracts of high purity in a much faster manner. Carbon dioxide (CO2) is generally preferred as a supercritical solvent because of its lower temperature requirements, better diffusivity and easy removal. The present study describes the characterization of supercritical CO2 extracts of Indian variety of Cordyceps sinensis(CS)-a high-altitude medicinal mushroom widely revered in traditional medicine for its extensive anti-hypercholesterolemic, anti-inflammatory, anti-proliferative and energy-enhancing properties. Experimental parameters viz. 300 and 350 bar of extraction pressure, 60 ºC of temperature, 0.4L/h CO2 of flow rate and use of 1%(v/v) of ethanol as entrainer were optimized to prepare three different extracts namely, CSF1, CSF2 and CSF3. High-performance thin-layer chromatography (HPTLC) was used for assessing the quality of all the extracts in terms of cordycepin, the pivot biomarker compound in CS. Characterization by HPTLC and GC-MS confirmed the presence of flavonoids and nucleobases and, volatile organic compounds (VOCs), respectively. The chromatographic data acquired from metabolite profiling were subjected to chemometric analysis in an open source R studio which illustrated interrelatedness between CSF1 and CSF2 in terms of two major principal components. i.e. Dim1 and Dim2 whose values were 40.33% and 30.52% in variables factor map plotted using the HPTLC-generated retardation factor values. The factor maps based on retention times of the VOCs exhibited a variance of Dim1=43.95% and Dim2=24.85%. Furthermore, the extracts demonstrated appreciable antibacterial activity against Escherichia coli and Salmonella typhi by generation of reactive oxygen species(ROS), protein leakage and efflux pump inhibition within bacterial pathogens. CSFs were elucidated to be significantly cytoprotective (P<0.05) in a simulated hypobaric hypoxia milieu (0.5% oxygen). CSF2 showed the best results by effectively improving the viability of human embryonic kidney (HEK 293) cells to 82.36±1.76% at an optimum dose of 100µg/mL. Levels of hypoxia inducible factor-1 alpha (HIF-1α) were modulated four-fold upon supplementation with CSF2. The results collectively evinced that the CSF extracts are substantially bioactive and could be effectively utilized as mycotherapeutics for multiple bioeffects.